Sound Field Simulation and Optimization at an Underground Subway Station. Issue 3 (September 2013) - Tang, C.H.; Wang, Y.S.; Guo, H.
The noise of underground subway stations has a great influence on the passengers and workers. The finite-element based software Actran is introduced to analyze the acoustical performance of an underground subway station in this paper. A sample station named Xingzhong Road from metro line 9 in Shanghai is considered. The finite element models for analysis of sound field characteristics are established at the two common working conditions of the subway train: coming and going. The sound pressure levels (SPLs) and energy distributions are calculated and verified by field noise tests. Based on the established models, furthermore, an optimizing scheme based on the orthogonal experimental algorithm is presented and performed. The simulation results show that the proposed method is effective and useful for improving the sound environment and reducing the harm of noise to the passengers and workers at underground subway stations.